(3QSGdI aj CYeGd GdGSWQdGHs - (3eMeO Hf MSjf GdMGQKj GdgeOGfj GdYGedj, HgGA GdOjf , J (B1031 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO agPg QSGdI ai GdGSWQdGH eTJedI Ydi SJjf HGHkG bGd HYV YdeGA gPG Gdaf ai MOG GdeSWM gh LSe eTJedI Ydi UaGjM s
(3BNQgG (B:s
(3hai CcKQ GdCSWQdGHGJ jQSehf gPg GdchGcH aef YQagG HMjK dGjbY ai GdGTJHGg JMUd dg GdcaGjI ai gPG GdHGH hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3hgPg GdQSGdI eNJUQI ef QSGdI cKjQI ddfUQ GdWhSi HGddZI GdaGQSjI HgG fXGe GdJYbjHIs
(3jdi GdeNWhW aGFOI ai HjGf cjajI GSJNQGL HYO GdchGcH heWGdYI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdadcs